The Role of Music in Different Cultures - Šramel, Saša (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines the role of music as a universal language that transcends cultural, linguistic, and geographical boundaries. Music plays a significant role in traditions, rituals, and daily life, acting as a medium for transmitting values, identity, and cultural heritage. A review of global musical traditions illustrates how music reflects social and historical contexts, from African drums as communication tools to Brazilian samba as a symbol of national pride. Exploring diverse musical traditions fosters empathy, respect, and an appreciation of diversity. The organization of music workshops and international festivals promotes cultural exchange; however, ensuring authenticity and equitable representation of musical traditions remains essential. Music continues to be one of the most powerful tools for strengthening social cohesion and promoting intercultural dialogue.